Biological Control of Cocoa Pod Borer (Conopomorpha cramerella Snell) Using Egg Parasitoids of Trichogrammatoidea bactrae fumata in East Java - Dwi Suci Rahayu; Endang Sulistyowati (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2018)
A study on the potential of  Trichogrammatoidea bactrae fumata  (Tbf) parasitization in the field was conducted at an insecticide-free cocoa cultivation namely Treblasala Plantation, Banyuwangi, East Java. The research design used was a factorial randomized block design with three replications. The tested treat-ments consisted of parasitoid release intervals (once in 2 and 4 weeks) and the release population of 0 (control); 25,000 and 50,000  Tbfper hectare per release. Observations were made on number of detected eggs and parasitized eggs, and level of cocoa damage caused by cocoa pod borer (CPB) attacks. The results of  this  research showed that parasitization level of  T.  bactrae fumata  on CPB eggs after3 months of the release ranged from 29.81–42.79%. The parasitoid release of CPB eggs (T. bactrae fumata) in the field for a year showed that the parasitiza-tion  level of CPB eggs in the field ranged from 17.78–29.72%. Nevertheless, during that year, there was no significant effect of parasitoid release on the suppression of yield loss due to CPB attacks in the field.